PENGEMBANGAN DESA PESISI DENGAN IMPLEMENTASI METODE EKONOMI SIRKULAR MELALUI PERATURAN DESA DALAM MENDUKUNG SUSTAINABLE DEVELOPMENT GOALs - Dirkareshza, Rianda; Nasution, Ali Imran; Taupiqqurrahman, Taupiqqurrahman; Hindira DPS, Ratna (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
As a village located on the coast, Pabean Udik Village has many problems which are covered in environmental hygiene aspects. This Community Service contains an environmental framework in supporting the circular economy concept, given the increasing interest of practitioners and theorists in the circular economy. The method of implementing this Community Service uses the Preparatory Stage which includes the process of field visits, handling priority issues and data collection and needs analysis followed by the Implementation Phase with Hearings, Compilation of Village Regulations and Peer Review. The results of the draft Village Regulations that had been prepared by the Service Team have been received by the Head of the Udik Customs Village which is expected to be resolved to become a legal umbrella as an effort to resolve the problem of disposing of garbage. the results of observations during the activity show that the importance of knowledge of the surrounding community about the importance of environmental cleanliness interspersed with qualified technology, especially through legal arrangements for payments related to bank waste. It is hoped that this service activity can be continued in the following year so that people can understand the importance of environmental cleanliness with the existence of a legal umbrella.